Evaluation of a HIV voluntary opt-out screening program in a Singapore hospital. - Xin Quan Tan; Wei-Ping Goh; Indumathi Venkatachalam; Diana Goh; Revathi Sridhar; Hwang Ching Chan; Sophia Archuleta (PLoS ONE)
Background Early diagnosis of human immunodeficiency virus (HIV) allows for appropriately timed interventions with improved outcomes, but HIV screening among asymptomatic persons and the general population in Singapore remains low. In 2008, Singapore's Ministry of Health implemented HIV voluntary opt-out screening (VOS) for hospitalised adults. We evaluated the outcome of VOS and surveyed reasons for its low uptake in our institution. Methods We assessed the outcomes of the VOS programme from January 2010 to December 2013 at National University Hospital, a 1081-bed tertiary hospital in Singapore. We also examined reasons for opting-in and opting-out using an interviewer-administered structured questionnaire in a representative sample in January 2013. Results 107,523 patients fulfilled VOS criteria and were offered HIV screening, of which 5215 (4.9%) agreed to testing. 4850 (93.1%) of those who opted-in had an HIV test done. Three (0.06%) tested positive for HIV. 238 patients (14.2%) were surveyed regarding reasons for opting-in or out of VOS. 21 (8.8%) had opted-in. Patients who opted-in were likely to be younger, more educated and reported having more regular sexual partners. Type of housing, number of casual sexual partners, sexual orientation, intravenous drug use, condom use and previous sexually transmitted infection were not associated with deciding to opt-in/out. Patients' most common reasons for opting-out were: belief that they were at low risk (50.2%), belief that they were too old (26.8%), cost (6.9%) and aversion to venepuncture (6.5%). The most common reason for opting-in was desire to know their HIV status (47.6%). Conclusion The success of an HIV-VOS program is largely determined by test uptake. Our study showed that the majority of eligible VOS patients opted-out of HIV screening. Given the considerable cost and low yield of this programme, more needs to be done to better equip patients in self-risk assessment and opting in to testing.